Diagnosis of Renibacterium salmoninarum infection in harvested Atlantic salmon (Salmo salar L.) on the east coast of Canada: Clinical findings, sample collection methods and laboratory diagnostic tests. Issue 5 (2nd March 2023) - Jia, Beibei; Burnley, Holly; Gardner, Ian A.; Saab, Matthew E.; Doucet, Adele; Hammell, K. Larry
Abstract: Chronic subclinical infection with the aetiological agent of bacterial kidney disease (BKD), Renibacterium salmoninarum, presents challenges for the clinical management of disease in farmed salmonids and for prevalence estimation. Harvested salmon sampled at processing plants provide the opportunity to describe subclinical outcomes of BKD using gross necropsy observations and diagnostic test results in farmed Atlantic salmon ( Salmo salar L.) populations that are apparently healthy (i.e. alive at harvest) but naturally exposed to R. salmoninarum infection. Sampling of farmed salmon (Population A, n  = 124 and Population B, n  = 160) was performed immediately post‐slaughter as fish were being processed at a plant in New Brunswick, Canada. Populations were selected based on planned harvests from sites with histories of recent exposure events related to clinical BKD as evidenced by the site veterinarian's diagnosis of mortality attributable to BKD: One site (Pop A) had recently increasing mortalities attributed to BKD, and the other site (Pop B) had ongoing low‐level mortalities with BKD pathology. As expected with the different exposure histories, Pop A had a higher percentage (57.2%) of R. salmoninarum culture‐positive kidney samples compared with similar fish samples in Pop B (17.5%). Diagnosis of R. salmoninarum by gross granulomatous lesions in internal visceral organs, bacterial culture and identification by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) using different swab transport methods, and molecular detection methods (quantitative PCR, qPCR) were compared. Agreement of culture‐positive percentages at the sample level was moderate (kappa: 0.61–0.75) among specimens collected using different kidney sampling methods in Pop A and Pop B. The highest proportion of R. salmoninarum ‐positive cultures occurred when kidney tissues were transported to the laboratory and inoculated directly onto agar using a swab (94% of cultures from Pop A and 82% from Pop B when fish were positive by any culture method). Fish with cumulative lesion scores (severity of granulomatous lesions in 3 different visceral organs) of >4 were all culture positive, and when compared with non‐lesioned fish, had substantially higher odds of being culture positive: Pop A: odds ratio (OR) = 73, 95% confidence interval (CI) (7.91, 680.8); Pop B: OR = 66, 95% CI (6.12, 720.7). Our study found that onsite postmortem examinations with severity scores of gross granulomatous lesions were predictive of positive culture results for R. salmoninarum, and they were a useful proxy for assessing prevalence in apparently healthy populations with subclinical infection .